A Multi-faceted, Fat-defending Peptide Hormone: Ghrelin - Cicek, Betul; Inanc, Neriman (Pakistan Journal of Nutrition, 2011)
Ghrelin is a novel gastric hormone recognized in 1999 as a mediator of growth hormone release. Ghrelin is a peptide hormone in which the third amino acid usually serine is modified by an acyl acid. This modification is essential for ghrelin’s activity. Ghrelin may thus be an essential hormone for maintaining growth hormone release and energy homeostasis. Ghrelin has profound orexigenic, adipogenic and somatotrophic properties, increasing food intake and body weight. Secreted predominantly from the stomach, ghrelin is the natural ligand for the growth hormone secretagogue receptor in the pituitary gland, thus fulfilling the criteria of a brain-gut peptide. Ghrelin is an important component of an integrated regulatory system of growth and metabolism acting via the vagus nerve and is implicated in a variety of altered energy states as obesity, eating disorders, neoplasia and cachexia. It also enhances immune responses and potentially down-regulates anti-inflammatory molecules. The discovery of ghrelin has increased the current knowledge on feeding regulation, nutritional homeostasis and metabolic processes.